FAKTOR KOREKSI VOLUME DOLOK YANG DIUKUR DI SUNGAI (LOGPOND) (Correction factor of logs volume meaured in logpond) - Wesman Endom; Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Measuring the volume of logs which have been rafted on the rivers is very difficult. The difficulty is mostly in measuring the average top and bottom diameters of logs because the largest portion of logs are inside the water.In this paper, the results of measurements carried out both on the ground and in the river are described. Lately, log measurement in the river is necessary because:a. Volume of logs sent to industries would be measured in the river.b. Many logs of the illegal cutting found are rafted in the river.The observation reveals that :1. Volumes of logs measured on the ground and in the river are significantly different.2. From the sample of 60 logs of Dryobalanops spp. it is found that the total volume measured on the ground is 273,18 m3, while the total volume measured in the river is 262, 76 m3. The total difference is 10,42 m3 or 0,04 m3 per_m3 in average.3. the correction factor (FK) then is 0,04 m3 per m3 or 3,81 %. It means that the volume of log measured in the river is smaller than the volume Measured on the ground. Therefore, the volume measured in the river should be multiplied with the correction factor of 1.04 to obtain the real volume as measured on the ground.